Effect of protein ingestion on splanchnic and leg metabolism in normal man and in patients with diabetes mellitus. - Wahren, J (1976)
The inter-organ flux of substrates after a protein-rich meal was studied in seven healthy subjects and in eight patients, with diabetes mellitus. Arterial concentrations as well as leg and splanchnic exchange of amino acids, carbohydrate substrates, free fatty acids (FFA), and ketone bodies were examined in the basal state and for 3 h after the ingestion of lean beef (3 g/kg body wt). Insulin was withheld for 24 h before the study in the diabetic patients. In the normal subjects, after protein ingestion, there was a large amino acid release from the splanchnic bed predominantly involving the branched chain amino acids. Valine, isoleucine, and leucine accounted together for more than half of total splanchnic amino acid output. Large increments were seen in the arterial concentrations of the branched chain amino acids (100-200%) and to a smaller extent for other amino acids. Leg exchange of most amino acids reverted from a basal net outut to a net uptake after protein feeding which was most marked for the branched chain amino acids. The latter accounted for more than half of total peripheral amino acid uptake...